The Effect of Contextual Worksheets Assisted MEA Learning on Critical and Creative Thinking Ability - Astawa, I Wayan Puja; Kusuma Sari, I G A Sri; Sudiarta, I Gusti Putu (Universitas PGRI Madiun, 2020)
The ability to think critically and creatively is needed in solving math problems. Secondary school students in Indonesia still possess these two abilities according to the results of PISA research. Therefore, learning studies that influence these two abilities are still feasible to do. This study aims to examine the effect of MEA learning with contextual worksheets on the ability to think critically and creatively in solving math problems. The study was a quasi-experimental study using a post-test only control group design. The research population consisted of 137 class X students of SMK Kharisma Mengwi, Badung Regency, Bali for the 2019/2020 school year, which was spread into five classes with equivalent math abilities. A random sampling technique determined a sample of 2 classes. Data on the ability to think critically and creatively in solving mathematical problems were collected using a test in the form of a description. Data were analyzed using the MANOVA test. The results of the analysis show that MEA learning with contextual worksheets has a positive effect on the ability to think critically and creatively in solving math problems (F = 90.018; p <0.05).